Cryostat system for investigation on new neutron moderator materials at reactor TRIGA PUSPATI - Dris Z.B.; Mohamed A.A.B.; Hamid N.A.; Azman A.; Ahmad M.H.A.R.M.; Jamro R.; Yazid H. (American Institute of Physics Inc., 2023)
A simple continuous flow (SCF) cryostat was designed to investigate the neutron moderation of alumina in high temperature co-ceramic (HTCC) and polymeric materials such as Teflon under TRIGA neutron environment using a reflected neutron beam from a monochromator. Cooling of the cryostat will be carried out using liquid nitrogen. The cryostat will be built with an aluminum holder for moderator within stainless steel cylinder pipe. A copper thermocouple will be used as the temperature sensor to monitor the moderator temperature inside the cryostat holder. Initial measurements of neutron spectrum after neutron passing through the moderating materials have been carried out using a neutron spectrometer. 2016 AIP Publishing LLC.